NEW TRENDS IN TEACHING THE THEORY OF MANUFACTURING AT UNIVERSITIES - MURCINKO, Jaromir (Trends in education, 2012)
The paper dealt with new approaches in field of teaching technological subjects at universities. The present available systems in diagnostics and informatics are used in monitoring and evaluation of manufacturing process. The paper describes suggestion of workplace for monitoring and evaluation that is connected to internet. The realized experiments are watched, monitored, analysed and evaluated that allows for students information access without restrictions even in repeated regime.
Keywords: interaction; manufacturing process; WiFi device; knowledge.